The Application of Maxim Quantity in Explaining Tourist Objects by Diploma 3 Students of Tour and Travel Department - Paramita Sari, Ni Luh Komang Julyanti; Jokosaharjo, Sulistyoadi; Prayogi, Putu Agus (Akademi Komunitas MAPINDO, 2023)
The history and culture of Bali has become an additional value for the development of Bali tourism. In addition to natural beauty such as the sea and mountains, local wisdom which is still upheld by the people of Bali makes Bali a special place for the tourists who are visiting Bali Island. Tourism in Bali is one of the economic sectors that the Balinese people are most involved in. One of the jobs in the tourism sector that many Balinese people are involved in is a tour guide. Good communication skills are very necessary for tourism workers, one of the languages which is commonly used is English. The application of the principle/maxims of quantity in the utterances of tour guides is the subject of study in this study. The research objects in this study were 21 diploma students majoring in tour and travel department at Triatma Mulya University. This research is a qualitative research that analyzes the application of the maxims/principles of quantity in students' utterances while explaining tourist objects. The data obtained will be sorted and processed based on pragmatic theory and then it would be presented descriptively. During the explanation of tourist objects, students have applied the principle of quantity in several utterances that are spoken. However, some of the students' speeches did not apply the principle/maxim of quantity. This happened because in processing utterances students were mostly influenced by internal factors such as the language factor that is possessed by students were still limited and the mastery of content components. Students' unpreparedness during practice is one of the inhibiting factors for students to apply the principle/maxims of quantity to their utterances.Keywords: communication, tour guide, pragmatic, speech, maxim of quantity